An Empirical study on the relationship between credit rating and banks´ performance: evidence from an emerging market - Abu-Alkheil, A.; Khartabiel, G.; Riaz, A.; A-Khan, W. (International Journal of Accounting & Business Finance, 2023)
This paper provides new empirical evidence with respect to the influence of banks´ long- and short-term credit ratings and their volatility performance in the emerging market of Pakistan covering 10-year analysis and a unique and comprehensive data set derived from a sample of Islamic and conventional banks with Islamic windows. The purpose of this paper is to examine the nature of the relationship between Islamic banks´ performance and banks´ credit rating focusing on the emerging market of Pakistan over the period of 2010-2019. To achieve the describing goal, researchers use various quantitative approaches, namely the ordinary least square (OLS) and the Granger causality test. Sample consists of nine conventional banks with Islamic windows and three fully-fledged Islamic banks listed on the Karachi Stock Exchange with credit ratings assigned by the PACRA. Results reveal that banks with higher financial performance have higher long- and short-term ratings, higher GDP growth rates, lower equity to assets ratio, and are smaller in size. Results also array the existence of bidirectional Granger causality between short- and long-term ratings and ROE and a unidirectional Granger causality between trend ROE and trend short- and long-term ratings, respectively.
Keywords: Banks Performance; Credit Rating; Event Study; Islamic Banking; Risk